2020
DOI: 10.1007/s12192-020-01080-6
|View full text |Cite
|
Sign up to set email alerts
|

An inventory of interactors of the human HSP60/HSP10 chaperonin in the mitochondrial matrix space

Abstract: An inventory of interactors of the human HSP60/HSP10 chaperonin in the mitochondrial matrix space. Cell stress & chaperones, 25(3), 407-416.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…An integral part of this mitochondrial quality control system represents the mitochondrial chaperone heat shock protein 60 (HSP60). HSP60 interacts with its co-chaperone HSP10 and enables the proper folding of more than 300 mitochondrial matrix proteins and, thereby, mitochondrial function [ 2 , 3 ]. Important folding substrates of this complex include the antioxidative enzyme SOD2 or acyl-CoA dehydrogenases (e.g., medium-chain acyl-CoA dehydrogenase), suggesting that HSP60 influences obesity development by affecting oxidative stress and lipid utilization [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…An integral part of this mitochondrial quality control system represents the mitochondrial chaperone heat shock protein 60 (HSP60). HSP60 interacts with its co-chaperone HSP10 and enables the proper folding of more than 300 mitochondrial matrix proteins and, thereby, mitochondrial function [ 2 , 3 ]. Important folding substrates of this complex include the antioxidative enzyme SOD2 or acyl-CoA dehydrogenases (e.g., medium-chain acyl-CoA dehydrogenase), suggesting that HSP60 influences obesity development by affecting oxidative stress and lipid utilization [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A released protein may rebind until it achieves a native conformation (Liu et al, 2010;Gruber and Horovitz, 2016;Hayer-Hartl et al, 2016). Chaperonins fold essential proteins in chloroplasts, mitochondria, and bacteria, as does the related group II chaperonin (CCT/TRiC) found in the eukaryotic cytosol (Kerner et al, 2005;Yam et al, 2008;Zhao and Liu, 2018;Bie et al, 2020). Though some biochemical and genetic evidence suggests E. coli GroEL (Castanié-Cornet et al, 2014) and mammalian cytosolic CCT/TRiC (Génier et al, 2016) play a role in targeting, all known functions of Cpn60 involve folding stromal proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic analysis in purified HSP60-deficient mitochondria suggested that about 20% of mitochondrial-localized proteins are HSP60-dependent, meaning they rely on HSP60 to mediate correct protein folding in the mitochondria. A survey of HSP60-interacting proteins was recently performed in HEK293 cells using coimmunoprecipitation and mass spectrometry and identified more than 300 proteins (Bie et al, 2020), 46 of which including ALDH2, CPT2, IDH3A, and SUCLG2 were downregulated in mitochondria of HSP60-deficient cardiomyocytes (Fan et al, 2019). Furthermore, an assessment of the mitochondrial protein import and stability found that deletion of HSP60 has no effect on mitochondrial protein import.…”
Section: Hsp60 Is Essential For Maintaining Mitochondrial Function and Cardiac Physiologymentioning
confidence: 99%
“…It has been shown that human HSP60 and HSP10 form a symmetrical football complex (Nisemblat et al, 2015), whereas the bacteria homolog of HSP60, GroEL, is organized in two rings, producing a barrel-like structure (Ostermann et al, 1989;Horwich et al, 2006). A survey of interactors of the human HSP60 suggested that most HSP60-interacting proteins are localized to the mitochondrial matrix space and involved in various mitochondrial functions and metabolic pathways (Bie et al, 2020). Interestingly, accumulating studies have demonstrated that HSP60 is also localized in extramitochondrial compartments including the cytosol, plasma membrane, and extracellular space, as well as in blood circulation (Meng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%